PUBLIC PROCUREMENT -BETWEEN LEGAL CHALLENGE AND ECONOMIC NECESSITY - Adrian, Constantinescu (Anales Universitatis Apulensis Series Jurisprudentia; No 16 (2013): ANNALES UNIVERSITATIS APULENSIS - SERIES JURIPRDENTIA, 2013)
The harmonization of the European Union legislation regarding public procurement appears as necessary in order to ensure maximum transparency and efficiency in case of public money expenses. The basis of this mechanism should be the idea of free competition, non-discrimination, application of the same criteria and requirements for all economic agents. Applying this concept, even more so under the current economic situation, entails following some clear principles in the management of public funds. Keywords: European Union, public money expenses, economic agents